IT Support Desk using Salesforce Service Cloud - Siddique Ibrahim S P, Grahalakshmi R,Bharathi Priya A, Thamelnesan N (International Journal of Advanced Science and Technology, 2020)
In big organizations, when we purchase their product/service, they give us service support. If there is a problem with the product or the service, we can report it to the organization’s support or service desk unit. People normally raise a ticket, requesting the concerned person to solve the problem as quickly as possible. They use a ticketing system for raising the ticket. Traditional ticketing systems, which many companies use these days are not so efficient. They are time consuming and they do not provide any insights to correct the mistakes and develop the business. Our project done using the salesforce service cloud provides a smart ticketing platform with analytical abilities and automated processes. This not only saves time but also helps in developing the business and taking the organization to a higher level. Our project, IT support desk is implemented in salesforce platform. Salesforce offers platform as service and software as service